Iron homeostasis in the human body and nutritional iron deficiency and solutions in China. Issue 6 (9th September 2018) - Luo, Ting; Lei, Lin; Chen, Fang; Zheng, Shilian; Deng, Ze‐yuan
Abstract: Iron is one of the most abundant metals on earth and is essential to most life forms. Its level is tightly regulated, since iron does not have an excretion regulation pathway, and a high toxicity of free iron can lead to tissue damage. The purpose of this review is to summarize recent knowledge, allowing a better comprehension of iron homeostasis in human body. Two main iron regulation systems including iron‐regulatory protein (IRP)–iron‐responsive element (IRE) system, and hypoxia‐inducible factor (HIF) system are highlighted. Dietary factors which impact iron absorption in human body are discussed. China has experienced rapid economic growth over the past few decades, however, significant nutritional problems remain, especially iron deficiency. Therefore, another focus of the review article is to trace the cause of iron deficiency in China and propose some possible solutions: improving dietary diversity, food iron fortification, increasing the intake of iron nutritional supplements, and iron biofortification. Practical applications: Our review focuses on iron metabolism, the regulation of iron homeostasis in the human body, and how dietary food intake impacts iron absorption and metabolism, to provide an updated summary of the iron research. Iron deficiency in China and the potential reasons are discussed. One of the reasons might be related to a large amount of plant foods. We summarize recent reports of iron deficiency in China and suggest solutions to alleviate dietary iron deficiency.